Understanding Pottery Function - Skibo, James M. author. aut Link
IX, 192 p. 61 illus., 9 illus. in color.
Keywords: The 1992 publication of Pottery Function applied ethnoarchaeological data collected among the Kalinga and experiments to set forth the principles for the creation of pottery use-alteration traces (residue, carbonization, and abrasion). Analogous to lithic use-wear analysis, this study developed the method and theory making the connections between pottery use traces and function. At the 20th anniversary of the book, it is time to assess what has been done and learned. One of the concerns of those working in pottery analysis is that they are unsure how to “do” use-alteration analysis on their collection. Another common concern is understanding intended pottery function—the connections between technical choices and function. This book is designed to answer these questions using case studies from the author and many others who are applying use-alteration analysis to infer actual pottery function. The focus of Understanding Pottery Function is on how practicing archaeologists can infer function from their ceramic collection.